A Case Study Research of Fun Teaching Media for English Young Learners at Pakuniran Children Forum: English - Raudhatul Islam (JOEY: Journal of English Ibrahimy, 2025)
Teaching English for Young Learner was the target of the single unit in this reserach which focus on Pakuniran Children Forum. The objectives of this research were to analyse the strategy of using fun teaching media for English young learners and investigate the enthusiasm of the participants in the implementation at the Pakuniran Village Children Forum. A qualitative approach is required in this research to explore the specific type of phenomena, utilizing a case study design. The research was conducted in Pakuniran village, located in the Pakuniran district of East Java Province, Indonesia. Pakuniran was selected as the study area because, despite being one of the more remote regions in the district, there was a high level of enthusiasm among children for learning English. Data collection in this study was carried out using observation, semi-structured interviews, and document analysis. The result found that the interest of young learner when using fun teaching media at the Pakuniran Children Forum, as well as the strategies used in the implementation of fun teaching media. Therefore, the researcher would be able to understand foreign language learning in rural areas and optimize their role as an educator in that environment.